Alpha-Synuclein Is a Target of Fic-Mediated Adenylylation/AMPylation: Possible Implications for Parkinson's Disease. Issue 12 (31st May 2019) - Sanyal, Anwesha; Dutta, Sayan; Camara, Ali; Chandran, Aswathy; Koller, Antonius; Watson, Ben G.; Sengupta, Ranjan; Ysselstein, Daniel; Montenegro, Paola; Cannon, Jason; Rochet, Jean-Christophe; Mattoo, Seema
Abstract: During disease, cells experience various stresses that manifest as an accumulation of misfolded proteins and eventually lead to cell death. To combat this stress, cells activate a pathway called unfolded protein response that functions to maintain endoplasmic reticulum (ER) homeostasis and determines cell fate. We recently reported a hitherto unknown mechanism of regulating ER stress via a novel post-translational modification called Fic-mediatedadenylylation/AMPylation. Specifically, we showed that the human Fic (filamentation induced by cAMP) protein, HYPE/FicD, catalyzes the addition of an adenosine monophosphate (AMP) to the ER chaperone, BiP, to alter the cell's unfolded protein response-mediated response to misfolded proteins. Here, we report that we have now identified a second target for HYPE—alpha-synuclein (αSyn), a presynaptic protein involved in Parkinson's disease. Aggregated αSyn has been shown to induce ER stress and elicit neurotoxicity in Parkinson's disease models. We show that HYPE adenylylates αSyn and reduces phenotypes associated with αSyn aggregation invitro, suggesting a possible mechanism by which cells cope with αSyn toxicity. Graphical abstract: Unlabelled Image Highlights: Aggregated forms of the presynaptic protein αSyn cause neurotoxicity and induce ER stress in cellular and animal models of Parkinson's disease. We have identified αSyn as a novel target for the human Fic protein, HYPE, a key regulator of ER homeostasis. HYPE adenylylates αSyn and reduces the aggregation of recombinant αSyn. Fic-mediated adenylylation/AMPylation is a possible mechanism by which cells cope with αSyn toxicity.